Swimming endurance of mice administered black tea extract and chicken egg powder - Deswati, Dyta Andri; Maryati, Maryati (Jurnal Penelitian Teh dan Kina, 2017)
Research of swimming endurance on mice administered black tea extract and chicken egg powder was carried out. The aim of this research was to evalute natatory exhaustion mice administered black tea extract, chicken egg powder and its combinated. The result of this research shown that mice administered of black tea extract and chicken egg powder have a swimming endurance 3.25 minutes and 3.01 minutes. Mice which administered combination of black tea extract and chicken egg powder have a swimming endurance 4.80 minutes. Generally, mice which administered combination of black tea extract and chicken egg powder have a swimming endurance more better than mice which administered of black tea extract and chicken egg powder individually.